Perbedaan MBSR dan Terapi Musik untuk Menurunkan Stres pada Pasien Kanker Payudara di Era Pandemi COVID-19 - Nur Arifah Astri; Tintin Sukartini; Hanik Endang Nihayati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the differences in the effectiveness of MBSR and music therapy in reducing the stress level of breast cancer patients in the COVID-19 pandemic era. The method used is a systematic review using the Scopus, ScienceDirect, Web of Science, PubMed and CINAHL databases. The JBI critical assessment checklist was used to assess the methodological quality of the included randomized controlled trials. The results showed that the MBSR intervention was carried out in 4-12 weeks, while music therapy was carried out in 12-40 minutes. MBSR and music therapy can reduce stress in breast cancer patients, but MBR therapy is more effective in the long term. In conclusion, MBSR and music therapy can be used as psychological therapy for breast cancer patients during the COVID-19 pandemic. Keywords: Breast Cancer, MBSR, Stress, Music Therapy